POTENSI KAWASAN WISATA DUSUN SUNGAI BUNGO SEBAGAI ATRAKSI WISATA DI KABUPATEN ROKAN HULU - Yati, Yuni; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine: (1) The potential of cultural tourism attractions Rokan Hulu; (2) The potential of the natural tourist attraction as a tourist area Rokan Hulu; (3) The government's efforts to develop tourist attractions.This study used a qualitative method with descriptive approach, this subjects of this study werw taken from including, local community and village heads of Sungai Bungo village. The data collection is made by a study of documents, observation, interview, documentation.The results showed that Sungai Bungo village has tourism potential, nature tourism attractions and cultural tourism attractions, the potential of natural attractions, consist Sampuran Rura Pattasan waterfall, forest, the potential culture attraction and surrounding a tourist area of traditional and unique village including customs ie fish depths of prohibition, aqikah, circumcision apostles / circumcisions, belimau kasai, marriage tradition and way of life, this village has a high social life marked by frequent public conduct mutual cooperation. In conclusing Sungai Bungo village was potentially to be developed as a tourist village, supported by the efforts to develop infrastructure improvements as well as promotion.Keywords : Tourist area, attraction, Sungai Bungo village